2021
DOI: 10.1016/j.neo.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional signatures underlying dynamic phenotypic switching and novel disease biomarkers in a linear cellular model of melanoma progression

Abstract: Despite advances in therapeutics, the progression of melanoma to metastasis still confers a poor outcome to patients. Nevertheless, there is a scarcity of biological models to understand cellular and molecular changes taking place along disease progression. Here, we characterized the transcriptome profiles of a multi-stage murine model of melanoma progression comprising a nontumorigenic melanocyte lineage (melan-a), premalignant melanocytes (4C), nonmetastatic (4C11-) and metastasis-prone (4C11+) melanoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…As mentioned before, our melanoma progression cellular model was established through continuous stress instead of genetic manipulation, resulting in epigenetic alterations both very early and late in tumor progression as previously described [ 12 , 13 ]. In a recent study, Preston‐Alp and colleagues showed that UV radiation alters DNA methylation both in primary human melanocytes and in murine melan‐a melanocytes in CpG sites found to be prognostic of overall survival of melanoma patients [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned before, our melanoma progression cellular model was established through continuous stress instead of genetic manipulation, resulting in epigenetic alterations both very early and late in tumor progression as previously described [ 12 , 13 ]. In a recent study, Preston‐Alp and colleagues showed that UV radiation alters DNA methylation both in primary human melanocytes and in murine melan‐a melanocytes in CpG sites found to be prognostic of overall survival of melanoma patients [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated a negative correlation between gene expression and promoter DNA methylation, but a positive correlation of gene expression with gene body DNA methylation [ 3 , 30 ]. Therefore, we analyzed previous data from RNA‐seq (transcriptome) [ 13 ] and ERRBS (methylome) of the four cell lines and integrated these data to unravel how methylation in different regions of the gene may affect gene expression. Our approach was to select genes that showed, in each comparison expression, changes positively correlated with alterations in gene body DNA methylation, as well as genes that showed a negative correlation between changes in expression and promoter DNA methylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This goes in line with the well-reported positive correlation of melanoma heterogeneity with stage progression. Consequently, increased genetic instability in the tumor causes transcriptomic and proteomic diversity, which in turn allows microenvironment-driven or cell-intrinsic phenotype-switching, i.e., reversible switching between different phenotypes of proliferative and invasive potentials [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%